The PENGARUH RELAKSASI OTOT PROGRESIF TERHADAP INTENSITAS NYERI MENSTRUASI MAHASISWA TINGKAT 2 AKADEMI KEPERAWATAN KESDAM ISKANDAR MUDA BANDA ACEH - Ratna Juwita; Eri Riana Pertiwi (Institut Teknologi, Sains, dan Kesehatan RS.DR. Soepraoen Kesdam V/BRW, 2023)
Introduction: Menstrual pain can inhibit the activities of adolescents so that there is a decrease in adolescent achievement at school. With the provision of progressive muscle relaxation techniques. can reduce a series of contractions and cause relaxation in certain muscles that can affect pain. This study aimed to determine the effect of progressive muscle relaxation in reducing pain intensity. Methods: This research is quasi-experimental research using a pre-posttest design approach. The population in this study was grade II students of Kesdam Iskandar Muda Nursing Academy that consists of 239 students. The total of sample was 42 students and selected by purposive sampling. This therapy is given on the first day to the third day of menstruation and performed twice a day for 15 movements for 30 minutes. Results: The majority of respondents aged 20 years reached 54.8%. The age of menarche was the majority of respondents 12 years reached 31.0%. The length of menstruation for the majority of respondents 1 to 6 days reached 71.4% and the duration of pain in 3-4 days reached 52.4%. The progressive muscle relaxation technique is effective in reducing menstrual pain (ρ=0.000). Conclusion: Progressive muscle relaxation technique is effective in reducing menstrual pain. It is hoped that with the involvement of health workers and families, they can apply effective progressive muscle relaxation techniques in the adolescents to reduce pain.